2020
DOI: 10.1186/s12866-020-1695-0
|View full text |Cite
|
Sign up to set email alerts
|

Larva of greater wax moth Galleria mellonella is a suitable alternative host for the fish pathogen Francisella noatunensis subsp. orientalis

Abstract: Background: Francisella noatunensis subsp. orientalis (Fno) is the etiological agent of francisellosis in cultured warm water fish, such as tilapia. Antibiotics are administered to treat the disease but a better understanding of Fno infection biology will inform improved treatment and prevention measures. However, studies with native hosts are costly and considerable benefits would derive from access to a practical alternative host. Here, larvae of Galleria mellonella were assessed for suitability to study Fno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Further tissue alterations, such as vacuolization and cytoplasmic fragmentation, follow the aforementioned pathophysiological consequences. These observations are in agreement with the literature, where mostly labeled and/or sample-destructive methods such as electron microscopy are applied for visualization 16,[46][47][48][49][50] . The advantage of the multimodal imaging method is that it is label-free and utilizes chemical contrast, such that infection-relevant changes can www.nature.com/scientificreports/ be followed during the initiation phase of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…Further tissue alterations, such as vacuolization and cytoplasmic fragmentation, follow the aforementioned pathophysiological consequences. These observations are in agreement with the literature, where mostly labeled and/or sample-destructive methods such as electron microscopy are applied for visualization 16,[46][47][48][49][50] . The advantage of the multimodal imaging method is that it is label-free and utilizes chemical contrast, such that infection-relevant changes can www.nature.com/scientificreports/ be followed during the initiation phase of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a study on the suitability of Galleria mellonella larva as an infection model for piscine francisellosis showed that early tetracycline treatment increases larval survival when infected with fish-isolated F. orientalis (previously Francisella noatunensis subsp. orientalis) (Djainal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we examined the pathogenic potential of the V. jasicida and V. rotiferianus in an insect infection model using G. mellonella larvae. This model has been shown to be a useful for studying human pathogenic Vibrio species as well as aquaculture Vibrio and non- Vibrio species ( Djainal et al., 2020 ; McMillan et al., 2015 ). The data here indicate that the strains of V. jasicida and V. rotiferianus tested are able to cause infection and mortality in G. mellonella , and this model could be used in the future to further investigate the virulence of these aquaculture pathogens.…”
Section: Discussionmentioning
confidence: 99%